Dramatic decrease of surgical emergencies during COVID-19 outbreak. Issue 6 (December 2020) - Rausei, Stefano; Ferrara, Francesco; Zurleni, Tommaso; Frattini, Francesco; Chiara, Osvaldo; Pietrabissa, Andrea; Sarro, Giuliano
Abstract : BACKGROUND: During the coronavirus disease 2019 (COVID-19) outbreak, a general decrease in surgical activity was observed. There is perception that this phenomenon has involved also surgical emergency, but no extensive data have been presented to date. The aim of this study was to analyze the real number of admissions and procedures for emergency surgical disease during COVID-19 pandemic. METHODS: This is a multicenter study including 18 general surgery units performing emergency surgery in hospitals of the "Red Zone" in Lombardy. Data about admissions from emergency department and surgical emergency procedures performed during March 2019 and March 2020 were collected in an online database. Additional data were collected according to the different indications for surgical treatment. The primary outcomes were the overall rate of admissions for emergent surgical disease and the overall rate of emergency surgical procedures in the study periods. The secondary outcome was the overall surgical rates (among all the diagnosed surgical diseases). RESULTS: Emergency surgical admissions and surgical operations significantly decreased with a fall in value of 45% ( p < 0.001) and 41% ( p = 0.001), respectively. This reduction was confirmed by the analysis according to different surgical indications, with the exceptions of admissions and operations for gastrointestinal bleeding and operations for abdominal trauma. The overall ratio between surgical procedures and diseases was not significantly different (54% vs. 63%; p = 0.619). This ratio was significantly different only for bowel obstruction and for gastrointestinal perforation. CONCLUSIONS: It seems correct to consider "true" the dramatic decrease of surgical problems during COVID-19 outbreak, despite any therapeutic strategies and logistic difficulties. LEVEL OF EVIDENCE: Epidemiological, level III. Abstract : Supplemental digital content is available in the text.